HIV Disclosure to Infected Children Involving Peers: A New Take on HIV Disclosure in the Democratic Republic of Congo - Faustin Nd. Kitetele; Wenche Dageid; Gilbert M. Lelo; Cathy E. Akele; Patricia V. M. Lelo; Patricia L. Nyembo; Thorkild Tylleskär; Espérance Kashala-Abotnes (MDPI AG, 2023)
Appropriately informing HIV-infected children of their diagnosis is a real challenge in sub-Saharan Africa. Until now, there is no consensus on who ought to disclose and how to disclose. This paper describes the model for HIV status disclosure in which HIV-positive children/adolescents are informed about their diagnosis in a process conducted by young peers under healthcare worker (HCW) supervision in a hospital in Kinshasa, the Democratic Republic of Congo. This new take on HIV status disclosure involving peers includes four stages that help the trained peer supporters to provide appropriate counseling, taking into account the age and level of maturity of the child/adolescent: the preliminary stage, the partial disclosure stage, the full disclosure stage, and the post-disclosure follow-up stage. Of all children/adolescents whose HIV status disclosure data were documented at Kalembelembe Pediatric Hospital (KLLPH) between 2004 and 2016, we found that disclosure by peers was highly accepted by parents, children/adolescents, and health workers. Compared to children/adolescents disclosed to by HCWs or parents, children/adolescents disclosed to by peers had (a) fewer depressive symptoms reported, (b) better drug adherence resulting in higher viral load suppression, and (c) a higher proportion of survivors on treatment. We found that involving peers in the disclosure process of HIV is an important approach to ensure adherence to treatment, resilience, and mental wellbeing of HIV-infected children/adolescents.